2007
DOI: 10.1007/bf02898151
|View full text |Cite
|
Sign up to set email alerts
|

High exposure of Chinese mercury mine workers to elemental mercury vapor and increased methylmercury levels in their hair

Abstract: Objective: The aim of this study was to determine the level of exposure of mercury (Hg) miners and smelter workers to elemental mercury (Hg 0 ) vapor in China, who work in Hg mines without using protective equipment against Hg 0 vapor. In addition, the level of methylmercury (MeHg) intake by the workers was estimated from the MeHg concentration in their hair.Methods: Urinary total mercury (THg) and hair THg and MeHg concentrations were measured in 26 Hg miners and smelter workers (i.e., exposed group), and 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…The main epidemiological methodologies used to study the health effects of environmental pollutants involve finding correlations between the levels of pollutant residues present in air, water, food, or certain compartments of the body and the incidences of specific allergic diseases [10,11]. While the above approach has provided a great deal of evidence regarding the deleterious effects of environmental pollution such as those associated with accidental or occupational contamination by lead, arsenic, or mercury (i.e., the effects of pollutants from point sources) [12,13], it has not proved as effective in studies investigating the effects of low concentrations of persistent organic pollutants such as polychlorinated biphenyls (PCBs) and dioxins (i.e., the effects of pollutants from nonpoint sources), which are frequently found among ordinary citizens, although some studies have suggested that exposure to the latter pollutants is associated with the risk of particular diseases [14,15]. This is because the health effects of environmental pollutants represent the end result of complex interactions between toxic chemicals and the physiological condition of vulnerable tissues, which is influenced by both the genetic background of the affected individual and their lifestyle, e.g., their diet and home environment [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The main epidemiological methodologies used to study the health effects of environmental pollutants involve finding correlations between the levels of pollutant residues present in air, water, food, or certain compartments of the body and the incidences of specific allergic diseases [10,11]. While the above approach has provided a great deal of evidence regarding the deleterious effects of environmental pollution such as those associated with accidental or occupational contamination by lead, arsenic, or mercury (i.e., the effects of pollutants from point sources) [12,13], it has not proved as effective in studies investigating the effects of low concentrations of persistent organic pollutants such as polychlorinated biphenyls (PCBs) and dioxins (i.e., the effects of pollutants from nonpoint sources), which are frequently found among ordinary citizens, although some studies have suggested that exposure to the latter pollutants is associated with the risk of particular diseases [14,15]. This is because the health effects of environmental pollutants represent the end result of complex interactions between toxic chemicals and the physiological condition of vulnerable tissues, which is influenced by both the genetic background of the affected individual and their lifestyle, e.g., their diet and home environment [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In Wuchuan, the average hair total-Hg and MMHg content of smelting workers was 69.3 and 2.32 mg kg − 1 , respectively, being significantly higher than that of subjects in a control group (0.78 mg kg − 1 and 0.65 mg kg − 1 , respectively) (Li et al, 2008d). Urinary Hg levels ranged from 22.6 to 4577 mg kg − 1 creatinine for the exposed workers and from 1.0 to 17.4 mg kg − 1 creatinine for the subjects in the control group (Sakamoto et al, 2007;Li et al, 2008d). Total-Hg concentrations in urine and hair from the exposed group displayed a significant correlation (r = 0.62), indicating adhesion of Hg vapour to hair (Sakamoto et al, 2007).…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…Urinary Hg levels ranged from 22.6 to 4577 mg kg − 1 creatinine for the exposed workers and from 1.0 to 17.4 mg kg − 1 creatinine for the subjects in the control group (Sakamoto et al, 2007;Li et al, 2008d). Total-Hg concentrations in urine and hair from the exposed group displayed a significant correlation (r = 0.62), indicating adhesion of Hg vapour to hair (Sakamoto et al, 2007). In Wanshan, Feng et al (2008) reported that concentrations of total-Hg and MMHg in hair samples collected from the residents ranged from 0.6 to 58.5 mg kg − 1 and 0.2 to 5.6 mg kg − 1 , respectively.…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…However, there is little epidemiological evidence to suggest that direct associations exist between exposure to low levels of environmental pollutants and adverse health effects in children. Epidemiological studies examining the health effects of environmental pollutants usually attempt to detect correlations between the levels of pollutants present in water, air, food, or particular organs and the frequencies of allergic conditions [6,7] and such methods have led to the adverse effects of environmental pollution being covered, e.g., those caused by lead, mercury, or arsenic contamination [8,9]; however, they have not proved as effective in studies investigating the effects of low concentrations of persistent organic pollutants such as PCBs and dioxins. However, some previous studies have detected associations between the risk of various conditions and exposure to such pollutants and the risk [10,11].…”
Section: Introductionmentioning
confidence: 99%